Kinesiophobia (fear of movement) level among patients with diagnosis of cervicogenic headache - Janusz Kocjan (Kazimierz Wielki University, 2017)
Introduction: Cervicogenic headache (CGH) is a syndrome characterized by chronic hemicranial pain that is referred to the head from either bony structures or soft tissues of the neck. Several previous studies reported limitation of physical activity among subjects suffer from headaches symptoms. However, still is little known about kinesiophobia phenomenon among patients with CGH symtoms. Purpose: The main purpose of the present study was to assess kinesiophobia level in this group of patients. Material and methods: A total of 47 CGH patients were examined. The control group consisted of 224 healthy subjects. Following questionnaires were used: Kinesiophobia Causes Scale (KCS), Visual Analogue Scale (VAS), Laitinen Pain Scale (LPS). Results: The mean values in KCS scale for each of study groups were as follows: DB [biological domain] = 36,3 ± 16,8 vs 24,7 ± 13,5; PD [psychological domain] = 52,6 ± 17,4 vs 24,7 ± 13,5; overall [KCS] = 44,5 ± 16,1 vs 32,3 ± 12,2. Significant correlation of headache severity with overall kinesiophobia index and kinesiophobia domains were noted. Conclusions: Overall kinesiophobia level is not higher in CGH group compared to control group. However the kinesiophobia level is strongly associated with headache severity.